Tag single nucleotide polymorphism rs1532624 located in cholesteryl ester transfer protein gene is associated with atherosclerosis cerebral ischemia - Lin Huang; Dan-Xin Wang; Li-Min Zhou; Tao Wang; Hai-Ying Zhang; Yun-Xia Zhang; Yin-Dong Zhang (Asian Pacific Journal of Tropical Medicine, 2018)
Objective: To investigate the relationship between polymorphisms of rs1532624 and rs289741 loci in cholesteryl ester transfer protein (CETP) genes and atherosclerotic cerebral infarction (ACI). Methods: The CETP gene rs1532624 and rs289741 in 95 patients with ACI and 177 healthy subjects were genotyped by MassARRAY mass spectrometry. Each locus genotype and allele frequency distributions were compared. Results: The difference of allele frequency distribution between the rs1532624 (χ2=1.723, P =0.189) and rs289741 (χ2=2.466, P =0.116) were not statistically significant. The frequency distribution of rs1532624 genotype between the cerebral infarction group and healthy control group was statistically significant (χ2=7.096, P =0.029), while rs289741 genotype frequency distribution between the two groups was not statistically significant (χ=2.906, P =0.234). Conclusion: ACI have a positive correlation with rs1532624 polymorphism, and AA genotype may be susceptible factors of ACI.